2020
DOI: 10.1177/1756284820980671
|View full text |Cite
|
Sign up to set email alerts
|

Technical and clinical outcomes of endoscopic retrograde cholangiopancreatography (ERCP) procedures performed in patients with COVID-19

Abstract: Background: The unprecedented situation caused by the coronavirus disease 2019 (COVID-19) pandemic has profoundly affected endoscopic practice in regard to access, volume, and workflow. We aimed to assess the potential changes in the technical outcomes of endoscopic retrograde cholangiopancreatography (ERCP) procedures carried out in patients with confirmed SARS-CoV-2 infection. Methods: We conducted an international, multicenter, retrospective, matched case-control study of ERCP procedures carried out in pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 23 publications
(29 reference statements)
0
14
0
Order By: Relevance
“…Whereas initially extreme and difficult to implement precautions were suggested for aerosol-generating procedures (including negative pressure rooms, hazmat suits, various protective devices [6] ), subsequent data has shown the potential for transmission during endoscopic procedures to be much lower than estimated [7] . In a previous multicenter study we found similar changes in volume and tactics in providing ERCP for patients with COVID-19 across 12 referral centers from Europe [8] , and other groups have described comparable adjustments to their workflow and protocols in response to the state of the outbreak in their countries [ 4 , 5 ].
Fig.
…”
mentioning
confidence: 69%
“…Whereas initially extreme and difficult to implement precautions were suggested for aerosol-generating procedures (including negative pressure rooms, hazmat suits, various protective devices [6] ), subsequent data has shown the potential for transmission during endoscopic procedures to be much lower than estimated [7] . In a previous multicenter study we found similar changes in volume and tactics in providing ERCP for patients with COVID-19 across 12 referral centers from Europe [8] , and other groups have described comparable adjustments to their workflow and protocols in response to the state of the outbreak in their countries [ 4 , 5 ].
Fig.
…”
mentioning
confidence: 69%
“…Similarly, a study reported the safety of ERCP procedures where ERCP was conducted for 18 patients who tested positive for COVID-19. The study compared COVID-19 and a control group with respect to complications of the ERCP procedure and found no significant impact on patient safety [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…They can be transmitted by respiratory droplets or faecal-oral, and they can also remain for a long time on surfaces contaminated with stool and endoscopic biopsy specimens (9,10). Healthcare workers are more vulnerable than the general population due to their high level of contagiousness, transmission routes, and long-term survival (9,11,13).…”
mentioning
confidence: 99%
“…Appointments and non-urgent procedures were postponed by following the instructions, and the number of endoscopic procedures decreased (12,13,14). It was observed that the postponing process increased the number of deaths and workload due to postponement after the pandemic (12,13,14).…”
mentioning
confidence: 99%
See 1 more Smart Citation